Facts About Riboflavin - R. Elaine Turner; Wendy J. Dahl (EDIS)
Did you know that mushrooms are a good source of riboflavin? Riboflavin is one of the B vitamins, also known as vitamin B2. We need riboflavin to use the carbohydrates, fats, and proteins in the foods we eat. Riboflavin helps us use these nutrients for energy in our bodies and additionally functions as an antioxidant. Riboflavin also is needed to properly use the vitamins niacin, folate, and vitamin B6. For more facts about riboflavin, check out this revised 2-page fact sheet written by R. Elaine Turner and Wendy J. Dahl, and published by the UF Department of Family, Youth and Community Sciences, April 2012.